Skip to content
Snippets Groups Projects
Commit 9b35a778 authored by Michael Wimmer's avatar Michael Wimmer
Browse files

fix some math

parent 419bc632
No related branches found
No related tags found
1 merge request!9DifferentialEquationsLecture2
Pipeline #43652 passed
This commit is part of merge request !9. Comments created here will be created in the context of that merge request.
...@@ -3,7 +3,7 @@ ...@@ -3,7 +3,7 @@
In the previous lecture, we focused on first order linear differential equations In the previous lecture, we focused on first order linear differential equations
as well as systems of such equations. In this lecture we switch focus to DE's as well as systems of such equations. In this lecture we switch focus to DE's
which involve higher derivatives of the function we would like to solve for. To which involve higher derivatives of the function we would like to solve for. To
facilitate this change we are going to change notation. In the previous lecture f`%acilitate this change we are going to change notation. In the previous lecture
we wrote differential equations for $x(t)$. In this lecture we will write DE's we wrote differential equations for $x(t)$. In this lecture we will write DE's
of $y(x)$, where $y$ is an unknown function and $x$ is the independent variable. of $y(x)$, where $y$ is an unknown function and $x$ is the independent variable.
For this purpose we make the following definitions, For this purpose we make the following definitions,
...@@ -57,64 +57,64 @@ $$y(x) = c_1 f_1 (x) + c_2 f_2 (x) + \cdots + c_n f_{n}(x). $$ ...@@ -57,64 +57,64 @@ $$y(x) = c_1 f_1 (x) + c_2 f_2 (x) + \cdots + c_n f_{n}(x). $$
To check that the $n$ solutions form a basis, it is sufficient to verify To check that the $n$ solutions form a basis, it is sufficient to verify
$$ det \begin{bmatrix} $$ det \begin{bmatrix}
f_1(x) & \hdots & f_{n}(x) \\ f_1(x) & \cdots & f_{n}(x) \\
f_1 ' (x) & \hdots & f_{n}'(x) \\ f_1 ' (x) & \cdots & f_{n}'(x) \\
\vdots & \vdots & \vdots \\ \vdots & \vdots & \vdots \\
f^{(n-1)}_{1} (x) & \hdots & f^{(n-1)}_{n} (x) \\ f^{(n-1)}_{1} (x) & \cdots & f^{(n-1)}_{n} (x) \\
\end{bmatrix} \neq 0.$$ \end{bmatrix} \neq 0.$$
The determinant in the preceding line is called the *Wronski determinant*. In The determinant in the preceding line is called the *Wronski determinant*. In
particular, to determine solutions, we need to find the eigenvalues of particular, to determine solutions, we need to find the eigenvalues of
$$**A** = \begin{bmatrix} $$A = \begin{bmatrix}
0 & 1 & 0 & \hdots & 0 \\ 0 & 1 & 0 & \cdots & 0 \\
0 & 0 & 1 & \hdots & 0 \\ 0 & 0 & 1 & \cdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\ \vdots & \vdots & \vdots & \cdots & \vdots \\
-a_0 & -a_1 & -a_2 & \hdots & -a_{n-1} \\ -a_0 & -a_1 & -a_2 & \cdots & -a_{n-1} \\
\end{bmatrix}.$$ \end{bmatrix}.$$
It is possible to show that It is possible to show that
$$det(**A** - \lambda \mathbbm{1}) = -P(\lambda),$$ $$det(A - \lambda I) = -P(\lambda),$$
in which $P(\lambda)$ is the characteristic polynomial of the system matrix $**A**$, in which $P(\lambda)$ is the characteristic polynomial of the system matrix $A$,
$$P(\lambda) = \lambda^n + a_{n-1} \lambda^{n-1} + \cdots + a_0.$$ $$P(\lambda) = \lambda^n + a_{n-1} \lambda^{n-1} + \cdots + a_0.$$
As we demonstrate below, the proof relies on the co-factor expansion technique As we demonstrate below, the proof relies on the co-factor expansion technique
for calculating a determinant. for calculating a determinant.
$$- det(**A** - \lambda \mathbbm{1}) = \begin{bmatrix} $$- det(A - \lambda I) = \begin{bmatrix}
\lambda & -1 & 0 & \hdots & 0 \\ \lambda & -1 & 0 & \cdots & 0 \\
0 & \lambda & -1 & \hdots & 0 \\ 0 & \lambda & -1 & \cdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\ \vdots & \vdots & \vdots & \cdots & \vdots \\
a_0 & a_1 & a_2 & \hdots & a_{n-1} + \lambda \\ a_0 & a_1 & a_2 & \cdots & a_{n-1} + \lambda \\
\end{bmatrix} $$ \end{bmatrix} $$
$$- det(**A** - \lambda \mathbbm{1}) = \lambda det \begin{bmatrix} $$- det(A - \lambda I) = \lambda det \begin{bmatrix}
\lambda & -1 & 0 & \hdots & 0 \\ \lambda & -1 & 0 & \cdots & 0 \\
0 & \lambda & -1 & \hdots & 0 \\ 0 & \lambda & -1 & \cdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\ \vdots & \vdots & \vdots & \cdots & \vdots \\
a_1 & a_2 & a_3 & \hdots & a_{n-1} + \lambda \\ a_1 & a_2 & a_3 & \cdots & a_{n-1} + \lambda \\
\end{bmatrix} + (-1)^{n+1}a_0 det \begin{bmatrix} \end{bmatrix} + (-1)^{n+1}a_0 det \begin{bmatrix}
-1 & 0 & 0 & \hdots & 0 \\ -1 & 0 & 0 & \cdots & 0 \\
\lambda & -1 & 0 & hdots & 0 \\ \lambda & -1 & 0 & cdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\ \vdots & \vdots & \vdots & \cdots & \vdots \\
0 & 0 & \hdots & \lambda & -1 \\ 0 & 0 & \cdots & \lambda & -1 \\
\end{bmatrix}$$ \end{bmatrix}$$
$$- det(**A** - \lambda \mathbbm{1}) = \lambda det \begin{bmatrix} $$- det(A - \lambda I) = \lambda det \begin{bmatrix}
\lambda & -1 & 0 & \hdots & 0 \\ \lambda & -1 & 0 & \cdots & 0 \\
0 & \lambda & -1 & \hdots & 0 \\ 0 & \lambda & -1 & \cdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\ \vdots & \vdots & \vdots & \cdots & \vdots \\
a_1 & a_2 & a_3 & \hdots & a_{n-1} + \lambda \\ a_1 & a_2 & a_3 & \cdots & a_{n-1} + \lambda \\
\end{bmatrix} + (-1)^{n+1} a_0 (-1)^{n-1}$$ \end{bmatrix} + (-1)^{n+1} a_0 (-1)^{n-1}$$
$$- det(**A** - \lambda \mathbbm{1}) = \lambda det \begin{bmatrix} $$- det(A - \lambda I) = \lambda det \begin{bmatrix}
\lambda & -1 & 0 & \hdots & 0 \\ \lambda & -1 & 0 & \cdots & 0 \\
0 & \lambda & -1 & \hdots & 0 \\ 0 & \lambda & -1 & \cdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\ \vdots & \vdots & \vdots & \cdots & \vdots \\
a_1 & a_2 & a_3 & \hdots & a_{n-1} + \lambda \\ a_1 & a_2 & a_3 & \cdots & a_{n-1} + \lambda \\
\end{bmatrix} + a_0$$ \end{bmatrix} + a_0$$
$$- det(**A** - \lambda \mathbbm{1}) = \lambda (\lambda (\lambda \cdots + a_2) + a_1) + a_0$$ $$- det(A - \lambda I) = \lambda (\lambda (\lambda \cdots + a_2) + a_1) + a_0$$
$$- det(**A** - \lambda \mathbbm{1}) = P(\lambda).$$ $$- det(A - \lambda I) = P(\lambda).$$
In the second last line of the proof we indicated that the method of co-factor In the second last line of the proof we indicated that the method of co-factor
expansion demonstrated is repeated an additional $n-2$ times. This completes the expansion demonstrated is repeated an additional $n-2$ times. This completes the
......
0% Loading or .
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment